Eurasian integration as an alternative strategy of the EU: Prospects for Development - A. V. Sorokina (Проблемы постсоветского пространства, 2017)
The article deals a new system of international relations after the collapse of the bipolar world in the post-Soviet space. The attention is focused on one of the features that characterize the current global development, regional integration of national states. The author concludes that the post-Soviet integration is only at the primary level in its development.